Using an Endovascular Strategy in the Open Setting: The Challenges of Hybrid Repair Using Frozen Elephant Trunk in an Extensively Dilated Aorta Associated with Coarctation - Harrington, Bertram; McPherson, Iain; Bayliss, Christopher; Barnard, Sion; McCaslin, James; Williams, Robin; Booth, Karen (AORTA, 2021)
With both stenosis and aneurysm, repairing a severely tortuous and coarcted aorta can present certain difficulties. The advent of hybrid arch frozen elephant trunk techniques, as well as other endovascular solutions, has produced safer surgical repair methods for such cases. We present the reconstruction and repair of a Type-1 thoracoabdominal aortic aneurysm using a staged approach in less-than-optimal anatomy. Interventions included hybrid frozen elephant trunk, balloon dilation, and thoracic endovascular repair.
Keywords: aortic arch; hybrid intervention; frozen elephant trunk; coarctation of the aorta; aneurysm